DAMPAK KETIDAKPATUHAN WAJIB PAJAK RESTORAN TERHADAP PENERIMAAN PAJAK DAERAH KABUPATEN WONOSOBO (2013-2016) - Sekar Kinasih, Era Agustin; Iswanaji, Chaidir; Prativi Nugraheni, Agustina (Jurnal Akuntansi dan Bisnis, 2022)
Local taxes are one of the original sources of income of the region. Taxes are an obligation given by the regions to the community as a form of state concern to increase the prosperity of the people so that they are better and develop. The reason for this study was to observe the amount of Local Tax Receivables, especially Restaurant Tax in Wonosobo regency government. The techniques used are qualitative techniques with information collection through research, virtual investigations, literature studies, and interviews (individual and aggregation). The type of evidence used is primary (principal) data and secondary data. Information collection through the interview stage with the Head of Public Services, Data, and Information of BPPKAD Wonosobo Regency. After several consultations, it was found that there were findings related to restaurant tax liabilities that were in arrears from 2013 to 2016. The drawback lies in the Wonosobo Regency Regional Regulation Chapter 11 article 13 of 2010 concerning Sanctions for Late Payment of Regional Taxes and Levies, as well as the consistency of the Wonosobo BPPKAD in providing a less firm response. The result of this study is that the level of bad receivables in Wonosobo Regency in 2013-2016 was in poor condition and fluctuated due to the ups and downs every year.